Further development of a parameterization for convective turbulent dust emission and evaluation based on field observations. Issue 17 (11th September 2014) - Klose, Martina; Shao, Yaping; Li, Xiaolan; Zhang, Hongsheng; Ishizuka, Masahide; Mikami, Masao; Leys, John F.
Abstract Further developments of a parameterization scheme for convective turbulent dust emission (CTDE) are presented. The scheme is advanced by including (1) a new statistical description of instantaneous momentum flux, (2) a correction function for cohesive force to account for the effect of soil moisture, and (3) a correction function for lifting force to consider the effect of vegetation roughness elements. The probability density function describing instantaneous momentum flux is now derived from large‐eddy simulations for different atmospheric stabilities. The vegetation correction function is based on a drag partition theory. Additional improvements on the representations of interparticle cohesive force and particle size distribution are introduced. The new CTDE scheme is tested against the field data obtained at a sand storm monitoring station in the Horqin Sandy Land in China in 2011 and during the Japan‐Australia Dust Experiment in Australia in 2006.